Munkaerő-piaci kihívások és az új generációk megítélése a magyar vállalatok szemszögéből = Labor market challenges and judging the new generation from the point of view of hungarian enterprises - Ilyés, Márton (Közép-Európai Közlemények, 2018)
One of the new constrain of the Central and Eastern European economies is labor shortage. Previously unemployment was the main social-economic challenge hence it was somewhat unexpected that workforce shortage has suddenly become a serious problem as well. Central and Eastern European countries can easily fall behind in the competition for workforce in the integrated European labor market. It is therefore particularly important to understand this phenomenon and to develop appropriate corporate and governmental responses to it. The classical theories of economics interpret the labor shortage as temporary situation where wage increases, changes in the composition of the economy’s structure, and technological development eliminate the shortage. However, adaptation takes time and can be painful, moreover it is also a question what the new balance is. This research is based a survey and provides a quantitative analysis about labor market challenges and especially about younger workers. Respondents are extremely negative in judging the qualifications and loyalty of younger generations. According to the managers, the development of the Hungarian education system is a key task for young people to be more involved in economic value creation. In the longer term, the demand for more educated workers can be projected. Those companies are already expanding better where more skilled workers are. According to companies, government could help with the reduction of taxes However active labor market policies would be useful as well.